effect of Aqueous extract of tobacco leaves on blood hemoglobin, mean corpuscular hemoglobin (MCH) and on mean corpuscular hemoglobin concentration (MCHC) in the red blood cells of Syrian Hamsters. - darious, Mohammed; ali, Ektimal; hammouda, Ruba (Latakia University Journal -Biological Sciences Series, 2018)
This study was performed to investigate the effect of aqueouse extract of tobacco leaves on blood parameters 15 Males Hamster were used in this study , they were divided into three groups : control , and two experimental groups ( five hamster in each ) , the control group was given distilled water , while the experimental groups were received oral doses of aqueouse extract of tobacco leaves 5.8 mg / kg of body weight and 11.8 mg / kg of body weight daily for (24)day . The Results showed a significant decrease (P <0.01) in the averages of each of the hemoglobin values , mean corpuscular hemoglobin( MCH ) and mean corpuscular hemoglobin concentrations ( MCHC ) in red blood cells of animals that received (5.8) mg / kg of body weight, and also in animals that received (11.8 ) mg / kg of body weight compared with the mean values of the control group. the proportion decrease using (5.8) mg / kg does was as follows : hemoglobin ( 22.09 % ) , MCH ( 7.12 % ) , MCHC ( 9.97 % ) . while the decrease proportion of hemoglobin , MCH , MCHC using the dose ( 11.8 ) mg / kg was as follows : (35.2 8 %), (12.46% ) , (12.60 % ) respectively . The results of the present study showed minimal changes in the average values of the numbers of white blood cells (increase or decrease) in animals given doses of the extract ( separately ) compared with the mean values of the control animals, and the differences were not significatives. تأثير المستخلص المائي لأوراق التبغ على هيموغلوبين الدم وعلى الهيموغلوبين الوسطي ( MCH ) وتراكيزه الوسطية (MCHC) في كريات الدم الحمر في الأقداد السورية (الهامستر ). أجريت هذه الدراسة لمعرفة تأثير المستخلص المائي لأوراق التبغ على بعض معايير الدم واستُخدم فيها ( 15 ) من ذكور الهامستر السوري . وزعت الحيوانات في ثلاث مجموعات : مجموعة شاهدة ومجموعتان تجريبيتان ( خمس في كل مجموعة ) ،جرّعت حيوانات المجموعة الشاهدة بالماء المقطر فقط ، في حين جرعت حيوانات المجموعتان التجريبيتان الأولى والثانية بجرعات يومية فموية من المستخلص المائي لأوراق التبغ ( 5.8 ملغ / كغ من وزن الجسم ) و( 11.8 ملغ / كغ من وزن الجسم ) ،لمدة ( 24 ) يوماً ، ثمّ أجريت التحاليل. بينت نتائج الدراسة انخفاضاً معنوياً (P< 0.01) في قيم متوسطات كل من الهيموغلوبين والهيموغلوبين الوسطي وتركيز الهيموغلوبين الوسطي في كريات الدم الحمر في مجموعة الحيوانات التي جرعت بالجرعة ( 5.8 ) ملغ /كغ من وزن الجسم , وأيضاً في مجموعة الحيوانات التي جرعت بالجرعة ( 11.8 ) ملغ /كغ من وزن الجسم بالمقارنة مع متوسطات القيم في المجموعة الشاهدة . وبلغت نسب التناقص باستخدام الجرعة( 5.8 ) ملغ / كغ كالآتي:الهيموغلوبين بمقدار 22.0 9 % ، MCH و بمقدار7.12 % ، و MCHC بمقدار 9.97 % و بلغت نسب تناقص الهيموغلوبين ،MCH وMCHC باستخدام الجرعة 11.8 ملغ / كغ على التوالي: 35.2 8 % ، 12.46% ،12.60 %.أظهرت نتائج الدراسة الحالية تغيرات ضئيلة في متوسطات قيم أعداد كريات الدم البيض ( انخفاضاً أو ارتفاعاً ) في الحيوانات المجرعة بالجرعتين السابقتين من المستخلص ( كل على حدة ) بالمقارنة مع متوسطات القيم في الحيوانات الشاهدة ، و لم تكن الفروق معنوية.